PERAN PENUGASAN RECEPTIONIST DALAM PENINGKATAN KOMPETENSI MENERAPKAN KETERAMPILAN KOMUNIKASI LISAN PADA SISWA DI SMKN 1 PROBOLINGGO - ALWI NUR H, HABIB (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2015)
Abstrack Verbal communication skill is an important skill that must be owned for every student. To apply this verbal communication, it can be improved through assignment method in practice. Assignment method is a way of presenting the teaching materials where the teacher gives certain task, so the student could perform learning activities and also take responsibility to acquire the skills.  This study aims to obtain the description of (1) the assignment of receptionist conducted in SMK Negeri 1 Probolinggo for Office Administration study program in academic year 2014/2015, (2) the role of students in improving the competence of applying verbal communication skills, and (3) student’s response to the assignment method become receptionist. Based on the result showed that (1) the assignment of receptionist conducted for student in SMK Negeri 1 Probolinggo has been done properly as the expectations, (2) the role of students in improving the competence of applying verbal communication skills can be performed through the receptionist assignment, and (3) the student’s response in performing the receptionist assignment on the average interpretation of respondents are in 82,6%. It can be concluded that the role of receptionist assignment in the improvement of competence applying in verbal communication skills students conducted in SMK Negeri 1 Probolinggo in academic year 2014/2015 declared performing well and in accordance with what had been expected.   Keywords: Verbal communication skill, receptionist, and receptionist assignment.